Anthropology, Science and Politics: Renewing the Vocation - Hann, Chris (Vilnius University Open Series, 2025)
In Germany, the discipline known traditionally as Völkerkunde or Ethnologie is currently (as a result of Anglophone dominance) being rebranded as Sozial- und Kulturanthropologie. Irrespective of the name, as a holistic field of enquiry, anthropology exemplifies the difficulties involved in demarcating boundaries between the humanities and the social and natural sciences. In the German language, all three are forms of science (Wissenschaft). Following these preliminaries, this paper draws on the celebrated ‘vocation’ lectures of Max Weber to probe the political dimensions of anthropological research. The possibility of a value-free science was precluded in socialist ideology, and it is again unfashionable nowadays wherever ‘activism’ supplants ‘academic’ agendas. In defending the Weberian ideal that stipulates the separation of the scholar from the politician, the chapter draws examples from various locations in Eurasia: Gypsies in Hungary, Uyghurs in China (Xinjiang), and finally Ukraine. It is important to maintain a dialogue with ‘local scholars’ subject to political constraints. Joint projects to test an agreed hypothesis may be an appropriate way to maintain conversations and advance knowledge. The chapter concludes with a personal note about the difficulties which arise in socialist and postsocialist Eurasia for a researcher from the West who is sympathetic to socialist ideals.